2022
DOI: 10.1530/eje-22-0211
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific pattern of white blood cell differential in endogenous hypercortisolism

Abstract: Objective: Endogenous hypercortisolism predisposes to impaired immune function and infections. To date, however, it is unknown whether there is a subtype-specific pattern in white blood cell (WBC) and WBC differential (WBCD) count. Methods: Retrospective monocentric cohort study in patients with overt endogenous Cushing’s syndrome (CS) or adrenal incidentalomas and autonomous cortisol secretion (ACS), with WBC/WBCD analysis at initial diagnosis and after biochemical remission. Cut-offs were obtained by recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Patients with advanced cancer usually experience a change in peripheral blood cell composition characterized by an expansion of the myeloid components and a reduction of the lymphoid components (Capone et al, 2018). Previous studies evaluating immune parameters in adrenal tumours reported significantly higher NLR in ACC than in non-malignant cases (Mochizuki et al, 2017;Gaitanidis et al, 2019;Sisman et al, 2020;Detomas et al, 2022). Moreover, studies of preoperative inflammation scores in patients with ACC who underwent resection of the primary tumour demonstrated a prognostic role of both NLR and PLR, although the cut-offs utilized and the results slightly differed between studies (Bagante et al, 2015;de Jong et al, 2021;Solak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with advanced cancer usually experience a change in peripheral blood cell composition characterized by an expansion of the myeloid components and a reduction of the lymphoid components (Capone et al, 2018). Previous studies evaluating immune parameters in adrenal tumours reported significantly higher NLR in ACC than in non-malignant cases (Mochizuki et al, 2017;Gaitanidis et al, 2019;Sisman et al, 2020;Detomas et al, 2022). Moreover, studies of preoperative inflammation scores in patients with ACC who underwent resection of the primary tumour demonstrated a prognostic role of both NLR and PLR, although the cut-offs utilized and the results slightly differed between studies (Bagante et al, 2015;de Jong et al, 2021;Solak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further interest in inflammatory parameters in ACC derives from the impact of endogenous hormonal secretion and/or exogenous steroid replacement therapy. Cortisol excess can affect white blood cell count and especially NLR and dNLR, due to its effect in increasing the neutrophils ( Detomas et al 2022 ). We assessed the presence of cortisol hypersecretion at treatment initiation, which was associated with worse survival, yet this was not confirmed at multivariable regression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce unnecessary screening and shorten the time of diagnosis, numerous attempts have been made including clinical scores ( 16 18 ), automated face recognition ( 19 21 ), radiological or clinical assessments of skin thickness ( 22 , 23 ), the quantification of facial plethora with near-infrared imaging ( 24 ), and, more recently, changes in white blood cell count ( 25 , 26 ). This mini-review focuses on the latest progress in clinical risk scoring system for CS.…”
Section: Introductionmentioning
confidence: 99%